THE IMPACT OF HISTORY LEARNING TO NATIONALISM AND PATRIOTISM ATTITUDES IN THE GLOBALISATION ERA - Subaryana, Subaryana (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2012)
Globalization is a process of interdependence almost in all life dimension of nations-state relationship and trans-national relations. In this case, it is not only capital, knowledge and technology but also social, political and cultural values of another country such as materialism, hedonism, individualism and pragmatism, have come to Indonesia, and influenced Indonesian people expecially teenagers. Recently, we can feel the national degradation that can be seen from the fading away the senses of nationalism and patriotism. Therefore, its efforts are needed to encourage the nationalism and patriotism character built up among the youth. One of the encouragement can be done through an effective history lesson. It isn’t intended to the understanding of history lesson as a process of entrophy but in this case the history lesson must be viewed as a progresive lesson and has a future view. So nationalism hoped here is not jenggoism or chauvinism but it is humanist nationalism, and not blind patriotism but it is constructive patriotism.